Possibility of impervious coating for the geotechnical reuse of soil and solid waste. Issue 5 (10th May 2019) - Inazumi, Shinya; Shishido, Ken-ichi; Soralump, Suttisak
Abstract : Impervious coating treatment is an original technology which consists of coating of soil and solid waste by particle units with an impervious coating material (a sealing material) containing water-absorbent polymers. The elution of attached substances, such as heavy metals, from the surface of soil particles is suppressed. This is because each particle is uniformly coated with the sealing material. Furthermore, because the sealing material swells, due to the absorption of pore water, and fills the void spaces of the soil and solid waste, the water interception performance of the treated soil can be expected to improve. Through laboratory experiments, this study evaluated the basic characteristics, such as the elution of heavy metals and hydraulic conductivity, of soil and solid waste that have been treated with an impervious coating in order to investigate their reutilisation.